Minimal heteroclinics for a class of fourth order O.D.E. systems. (August 2018) - Smyrnelis, Panayotis
Abstract: We prove the existence of minimal heteroclinic orbits for a class of fourth order O.D.E. systems with variational structure. In our general set-up, the set of equilibria of these systems is a union of manifolds, and the heteroclinic orbits connect two disjoint components of this set.